Feasibility of virtual surgical simulation in the head and neck region for soft tissue reconstruction using free flap: a comparison of preoperative and postoperative volume measurement. Issue 3 (March 2021) - Yokoi, S.; Nishio, N.; Fujimoto, Y.; Fujii, M.; Iwami, K.; Hayashi, Y.; Takanari, K.; Hiramatsu, M.; Maruo, T.; Mukoyama, N.; Tsuzuki, H.; Wada, A.; et al.
Abstract: In the head and neck region, preoperative evaluation of the free flap volume is challenging. The current study validated preoperative three-dimensional (3D) virtual surgical simulation for soft tissue reconstruction by assessing flap volume and evaluated fat and muscle volume changes at follow-up in 13 head and neck cancer patients undergoing anterolateral craniofacial resection. Patients received 3D virtual surgical simulation, and the volume of the planned defects was estimated by surgical simulation. Following en bloc resection of the tumor, the defect in the skull base was covered using a rectus abdominis myocutaneous flap. Following surgery, computed tomography scans were acquired at day 1 and at 6 and 12 months. Virtual planned defect was on average 227 ml (range, 154–315) and was 10% smaller than the actual flap volume in patients without skin involvement of the tumor. Between day 1 and 12 months post-surgery, the volume of fat and muscle tissue in the free flap dropped by 9% and 58%, respectively. Our results indicate that 3D virtual surgical simulation provides essential information in determining the accurate volume of the required free flap for surgical defect repair and may thus help improve surgical planning and functional and esthetic outcome.